2021
DOI: 10.1016/j.jcv.2021.104993
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 whole-genome sequencing using reverse complement PCR: For easy, fast and accurate outbreak and variant analysis.

Abstract: During the course of the SARS-CoV-2 pandemic reports of mutations with effects on spreading and vaccine effectiveness emerged. Large scale mutation analysis using rapid SARS-CoV-2 Whole Genome Sequencing (WGS) is often unavailable but could support public health organizations and hospitals in monitoring transmission and rising levels of mutant strains. Here we report a novel WGS technique for SARS-CoV-2, the EasySeq™ RC-PCR SARS-CoV-2 WGS kit. By applying a reverse complement polymerase chain reaction (RC-PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…Sequence reads were cleaned, trimmed and mapped to the SARS-CoV-2 Wuhan-Hu-1 reference genome (NC_045512.2). 7 For each sample, genomic variants were called and filtered by quality, with high quality variant calls being used to generate the consensus genome sequence for each sample. The consensus genome sequence was then processed using Pangolin, 8 a widely used computational tool that assigns the most likely lineage to a given SARS-CoV-2 genome sequence according to the Pango dynamic lineage nomenclature scheme.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence reads were cleaned, trimmed and mapped to the SARS-CoV-2 Wuhan-Hu-1 reference genome (NC_045512.2). 7 For each sample, genomic variants were called and filtered by quality, with high quality variant calls being used to generate the consensus genome sequence for each sample. The consensus genome sequence was then processed using Pangolin, 8 a widely used computational tool that assigns the most likely lineage to a given SARS-CoV-2 genome sequence according to the Pango dynamic lineage nomenclature scheme.…”
Section: Methodsmentioning
confidence: 99%
“…Samples with low RNA concentration (Ct ≥ 30) often produce low-quality or incomplete genomes without targeted intervention to improve the results of these samples 1214 .We observed that such high-Ct samples generally produce fewer on-target sequencing reads than low-Ct samples. Consequently, we wanted to test whether greatly increasing sequencing depth of these samples would allow high Ct samples to be reconstructed.…”
Section: Resultsmentioning
confidence: 85%
“…Samples with low RNA concentration (Ct ≥ 30) often produce low-quality or incomplete genomes without targeted intervention to improve the results of these samples [12][13][14] . We observed that such high-Ct samples generally produce fewer on-target sequencing reads than low-Ct samples.…”
Section: Assessment Of Over-sequencing Of High Ct Samples As a Strate...mentioning
confidence: 99%
“… 44 Novel whole‐genome sequencing technologies based on the EasySeqTM RC‐PCR SARS‐CoV‐2 WGS kit and RT‐PCR have proven to be useful for high‐throughput detection of mutant strains of SARS‐CoV‐2. 46 Vega‐Magaña et al designed three specific primers and probes for qRT‐PCR detection based on the N501Y, 69‐70del, K417N, and E484K S mutations, which played an important role in detecting the E484K mutation and P.2 mutant strains. 47 Exploiting the good selectivity and self‐quenching properties ascribed to molecular beacons, researchers developed a two‐tube multiplex qRT‐PCR detection method that can identify present viruses of concern (VOCs) via the detection of eight different mutation sites in the S protein.…”
Section: Nucleic Acid‐based Sars‐cov ‐2 Detectionmentioning
confidence: 99%